Comment naissent les mots ? (Signifiances (Signifying), 2022)
How are words born? This article envisages three possibilities.1. An Onomatopoeic origin. Some verbs have been formed from onomatopoeic words which convey the image of a blow. 2. Reference to the human body. This concerns such examples as the multiplicity of words, gravitating around the notion of “nose” and which contain a [nasal] segment. 3. Gesture Theory. The relationship between the notion of "curve" and the curved shape of the tongue when creating dorsals is examined in Arabic, Turkish and French. The motivated nature of the linguistic sign becomes evident provided that one formulates the reply in terms of phonetic features rather than phonemes.